Zero-dimensional bromobismuthate: Synthesis and characterization. (2022) - Roy Choudhuri, Jyoti; Pandey, Souvik
Abstract: A new inorganic-organic halobismuthate compound, hexabromobismuthate [BiBr6 ] 3− with counter organic cation N, N-dimethylanilinium ion has been isolated from reaction mixture. These hybrid materials are well established and exhibit opto-electronic properties. The new bromobismuthate compound was synthesized and properly characterized by single crystal XRD, IR and elemental analysis. The SCXRD experiments revealed that the compound has been crystalized in a monoclinic crystal system with the space group P 21/n and Z = 4.